BS ISO 965-4. ISO general purpose metric screw threads. Tolerances. Part 4. Limits of sizes for hot-dip galvanized external screw threads to mate with internal screw threads tapped with tolerance position H or G after galvanizing (22nd September 2020) - British Standards Institution,
No abstract available